2021
DOI: 10.1111/jai.14175
|View full text |Cite
|
Sign up to set email alerts
|

Consistency in the life history traits of four invasive pseudorasbora parva populations in Southern England

Abstract: Life history plasticity can be a strong predictor of the establishment and invasion success of introduced fishes. Here, the life‐history traits of four P. parva populations in adjacent ponds in Southern England were measured throughout 2013 to determine the timing and length of their reproductive season and the extent of trait plasticity. The relative abundance of the populations (as catch per unit effort) was similar, with low variability in their traits relating to reproductive effort and somatic growth. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…However, individuals belonging to older age classes (2+, 3+, 4+, and 5+) were caught in decreasing numbers, representing the natural mortality within populations. All sampled populations, except one, had a sex ratio biased towards males, as also found for invasive populations in England (Britton et al, 2007; Davies & Robert Britton, 2021). However, it should be stressed that for the population with the most unbalanced sex ratio (Firenze), only males were caught during the summer, leveraging the extreme sex ratio found.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…However, individuals belonging to older age classes (2+, 3+, 4+, and 5+) were caught in decreasing numbers, representing the natural mortality within populations. All sampled populations, except one, had a sex ratio biased towards males, as also found for invasive populations in England (Britton et al, 2007; Davies & Robert Britton, 2021). However, it should be stressed that for the population with the most unbalanced sex ratio (Firenze), only males were caught during the summer, leveraging the extreme sex ratio found.…”
Section: Discussionsupporting
confidence: 69%
“…The long reproductive period starts as early as April and lasts at least until late June. Previous studies showed that the annual gonadic cycle of P. parva has usually only one seasonal reproductive peak, corresponding to the warmest period of the year, but this period is considerably prolonged in both sexes, confirming a long reproductive season for this species, which also includes multiple depositions (Davies & Robert Britton, 2021; Gozlan et al, 2010; Záhorská & Kováč, 2009). Nevertheless, earlier spawning in spring and later spawning in autumn is not uncommon (Gozlan et al, 2010).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Topmouth gudgeon is an omnivorous fish [52][53][54], which feeds mainly on zooplankton and benthic animals in Lake Erhai [61]. The reproduction of the Japanese smelt population in Lake Erhai occurs mainly from January to April [47], which is earlier than that of the topmouth gudgeon [62]. Like most other fishes that have a zooplanktivores stage in their early life history [56], the full utilization of food during the reproductive stage of the Japanese smelt may reduce the growth of the topmouth gudgeon.…”
Section: Discussionmentioning
confidence: 99%
“…Non-native fish species can change receiving ecosystems through, e.g. increased predation pressure and competition for resources that can lead to shifts in ecosystem function and alteration of food webs (Gozlan et al 2010, Davies & Britton 2021). However, not all newcomers impose such changes, therefore, it is important to determine the traits that predict them to become successful invaders.…”
Section: Introductionmentioning
confidence: 99%